SENGKETA KEWENANGAN ANTARA KANTOR STAF PRESIDEN DENGAN WAKIL PRESIDEN DAN KEMENTERIAN KOORDINATOR NEGARA - Santika, Ni Luh Putri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 5 No 3 (2016), 2016)
This paper entitled “ Authority Di spute Between The Office of Presidential Staff with the Vice President and also Minister of State Coordinator ”. This paper uses normative analytical method with the statute approach and case approach . The Office of Presidential Staff is a new institution that born through Presidential Decree No. 26 of 2015. The chief of Presidential Staff was given authority by This Presidentian Decree to take control of the program priorities. It mean s that The Office of Presidential Staff have authority to make any programs and also do controlling and evaluating the ministers as routinely. Certainly this could potentially lead to dispute the authority with the Vice President and also Minister of State Coordinator . Presidential Staff ’s authority can not be bigger than Vice President, Minister of State Coordinator and also the ministers of state, because the authority expansion of the chief of Presidential Staff would reduce the authority of the Vice President and also Minister of State Coordinator . Establishment of the Office of Presidential Staff is the prerogative of the president in accordance with The 1945 Constitution of the Republic of Indonesia but t he authority which is granted to The Office of Presidential Staff is not in accordance with the constitution and legislation, especially in the law concerning the state ministries and the law concerning the Formation of Law and Regulations. President should reassess the institutional functions of P residential aide. The burden and responsibility of government should be enclosed by the Cabinet and ministry-level agencies. Makalah ini berjudul "Sengketa Kewenangan Antara Kantor Staf Presiden Dengan Wakil Presiden dan Kementerian Koordinator Negara ". Makalah ini menggunakan penelitian hukum normatif dan pendekatan undang-undang serta pendekatan kasus. Kantor Staf Presiden adalah lembaga baru yang lahir melalui Perpres Nomor 26 Tahun 2015. Perpres tersebut memberikan kewenangan kepada kepala Staf Kepresidenan untuk ikut mengendalikan program prioritas. Kewenangan tersebut juga berarti bahwa lembaga ini berwenang untuk membuat program sekaligus mengendalikan dan mengevaluasi rutin menteri-menteri. Hal ini tentunya berpotensi menimbulkan sengketa kewenangan dengan wakil presiden dan kewenangan yang dimiliki menteri koordinator. Kewenangan Staf Presiden tidak boleh lebih tinggi dari Wakil Presiden, menteri koordinator, dan menteri-menteri lainnya karena dengan diperluasnya kewenangan Kepala Staf Presiden akan mereduksi kewenangan Wakil Presiden dan para menteri koordinator. Pembentukan Kantor Staf Presiden merupakan hak prerogratif presiden yang sesuai dengan UUD NRI Tahun 1945 namun Kewenangan yang diberikan kepada Kantor Staf Presiden tidak sesuai dengan konstitusi dan peraturan perundang-undangan, terutama dalam UU Kementerian Negara dan UU Pembentukan Peraturan Perundang-undangan. Presiden semestinya mengkaji kembali fungsi kelembagaan pembantu presiden. Seharusnya beban dan tanggung jawab pemerintahan seharusnya sudah terwadahi dengan adanya pemerintah di Kabinet dan badan-badan setingkat kementerian.
Keywords: Authority Dispute; The Office of The Presidential Staff; The Vice President; Minister of State Coordinator; Sengketa Kewenangan; Wakil Presiden; Menteri Koodinator Negara; Kantor Staf Presiden